Policy Paper : Improvement to Fulfill Needs Health Services for Jember Residents Towards Universal Health Coverage : (Policy Paper : Improvement Pemenuhan Kebutuhan Pelayanan Kesehatan Bagi Penduduk Jember Menuju Universal Health Coverage) - Maya Puspitasari, Febriana (International Journal of Regional Innovation, 2024)
This policy paper aims to provide policy recommendations for making improvements in meeting the health service needs of Jember residents towards Universal Health Coverage. So as to encourage improvements in efforts to fulfill health services for Jember residents which are not yet in accordance with the mandate of Law Number 40 of 2004 concerning the National Social Security System and Presidential Instruction Number 1 of 2022 concerning Optimizing the Implementation of the National Health Insurance Program in fulfilling services promotive, preventive, curative and rehabilitative health through Universal Health Coverage. In accordance with presidential instructions and this law, by 2024 Universal Heath Coverage is targeted to reach 98% of the population. Meanwhile, Jember Regency currently has the lowest achievement in East Java Province, namely 71.20%. This condition is very unequal to the condition of the population of Jember Regency, which is the Regency with the highest prevalence of Stunting, Maternal and Infant Mortality in East Java Province. So far, the Jember Regency Government has provided guaranteed health services using a free, curative health service program called J-Pasti Keren. Universal Health Coverage is considered important to improve the community satisfaction index which still gets a "C" in the performance of the Health Service and also to reduce maternal and infant mortality rates and the prevalence of stunting in Jember Regency. This requires support in prioritizing handling of these problems, especially in the budgeting system. It is very important to make improvements so that the health service needs for Jember residents towards Universal Health Coverage. The methodology used in preparing this policy paper is SWOT analysis. So that policy alternatives can be obtained in order to improve the fulfillment of health service needs for Jember residents towards Universal Health Coverage. From the analysis carried out, recommendations and strategies can be formulated to improve the fulfillment of the health service needs of the Jember population towards Universal Health Coverage in accordance with the National Medium Term Development Plan and the mandate of the Law and Presidential Instructions, as well as supporting the acceleration of achieving the SDGs for Indonesia. Improvement in meeting health service needs for Jember residents. The recommendation given for making improvements is to shift the budget for free J Pasti Keren health services which are curative in nature to the Universal Health Coverage budget for the residents of Jember Regency, so that health services to the people in Jember Regency are also preventive, promotive, curative and rehabilitative. Apart from that, it also makes Universal Health Coverage a priority in the 2024 APBD Amendment so that it can meet the urgency of meeting the needs of health services for Jember residents towards Universal Health Coverage in 2024. Jember Regency Government, East Java Province, IndonesiaThis is a new author guidelines and article template of International Journal Of Regional Innovation. Article should be started by title of article followed by Authors Name and Affiliation Address and abstract number of words 100-250. Special for the abstract section, single spacing should be used between lines in this article. Article written in English. The abstract should be typed as concise as possible and should be composed of: problem statement, method, scientific finding result, and short conclusion. The abstract should only be typed in one paragraph and one-column format. Policy paper ini bertujuan untuk memberikan rekomendasi kebijakan dalam melakukan improvement pemenuhan kebutuhan pelayanan kesehatan bagi penduduk Jember menuju Universal Helath Coverage, demi mendorong adanya perbaikan terhadap pemenuhan pelayanan kesehatan bagi penduduk Jember sesuai dengan amanah Undang-Undang Nomor 40 Tahun 2004 tentang Sistem Jaminan Sosial Nasional dan Instruksi Presiden Nomor 1 Tahun 2022 tentang Optimalisasi Pelaksanaan Program Jaminan Kesehatan Nasional serta RPJMN . Dimana telah ditargetkan bahwa cakupan Universal Health Coverage pada tahun 2024 sebesar 98% untuk mewujudkan pelayanan kesehatan promotif, preventif, kuratif dan rehabilitative di Indonesia dan mencapai SDGs. Kondisi ini sangat timpang dengan kondisi penduduk Kabupaten Jember yang merupakan Kabupaten dengan prevalensi stunting, kematian ibu dan bayi tertinggi se-Provinsi Jawa Timur. Kabupaten Jember saat ini memiliki capaian Universal Health Coverage terendah se-Provinsi Jawa Timur yaitu sebesar 71,20%. Selama ini Pemerintah Kabupaten Jember memberikan jaminan pelayanan kesehatan dengan menggunakan program pelayanan kesehatan gratis J-Pasti Keren yang bersifat kuratif apabila penduduknya sakit. Sementara Universal Health Coverage dipandang penting untuk menurunkan prevalensi stunting, angka kematian ibu dan bayi di Kabupaten Jember dan memperbaiki indeks kepuasan masyarakat terhadap pelayanan kesehatan yang masih mendapatkan nilai “C”. Hal tersebut memerlukan dukungan dalam memprioritaskan penanganan masalahnya, terutama pada sistem penganggaran. Sangat penting untuk melakukan sebuah improvement sehingga kebutuhan pelayanan kesehatan bagi penduduk Jember menuju Universal Health Coverage dapat terpenuhi. Metodologi yang digunakan dalam proses penyusunan policy paper ini menggunakan analisa SWOT. Dengan menyoroti faktor internal yaitu Kekuatan (Strengths) dan Kelemahan (Weakness), serta faktor eksternal yaitu Peluang (Opportunities) dan Ancaman (Threat), maka dapat diperoleh alternatf kebijakannya. Metode SWOT diintegrasikan ke dalam pola fikir Policy Paper dari data primer dan data sekunder. Dari analisis yang dilakukan dapat dirumuskan rekomendasi strategi kebijakan dalam melakukan improvement pemenuhan kebutuhan pelayanan kesehatan penduduk Jember menuju Universal Health Coverage. Improvement Pemenuhan Kebutuhan Pelayanan Kesehatan Bagi Penduduk Jember. Rekomendasi yang diberikan dalam melakukan improvement yaitu dengan melakukan pergeseran anggaran pelayanan kesehatan gratis J Pasti keren yang bersifat kuratif ke anggaran Universal Health Coverrage bagi penduduk Kabupaten Jember, sehingga pelayanan kesehatan kepada masyarakat di Kabupaten Jember juga bersifat preventif, promotif, kuratif dan rehabilitative. Selain itu juga menjadikan Universal Health Coverage sebagai prioritas dalam Perubahan APBD (PAPBD) Tahun 2024, sehingga dapat memenuhi urgensi Pemenuhan Kebutuhan Pelayanan Kesehatan Bagi Penduduk Jember menuju Universal Health Coverage pada tahun 2024.